Assessment of the needs of student nurses regarding critical thinking in nursing practice - Pretoruis, Louise; Van Dyk, Agenes; Small, Luis; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2016)
This study involved a quantitative, quasi-experimental and contextual design. The target population for this phase was senior student nurses registered at the University of Namibia, in their fourth year of nursing studies in the training hospitals of Windhoek and Oshakati. A total of 46 fourth-year nursing students, registered at the Faculty of Medical and Health Sciences in the Department of Nursing, were included for phase 1 except for the two students who took part in the pilot study. The students were from both campuses, namely the Windhoek and Oshakati campuses, doing the four-year Diploma in Comprehensive Nursing curriculum, which incorporates the principles of critical thinking. An imaginary case scenario was developed for students to analyse and answer some relevant questions to enable the researcher to determine the level of understanding and integration of critical thinking. In this study each studentâ€™s answers were deductively analysed by calculating central values, more specifically the mean for each question, to determine their application of critical thinking skills in the management of a nursing problemThe researcher has, with literature support, arrived at â€œumbrellaâ€ concepts, namely the most important concepts that nurses in Namibia need and without which they cannot practice. These umbrella concepts are to be included in the educational programme.